Locus of control and Student Achievement - Sujadi, Eko; Latifa Aulianisya (Indonesian Journal of Counseling and Development, 2020)
Abstract. Locus of control is one of the personality characteristics possessed by humans. Locus of control can be divided into two, namely internal locus of control and external locus of control. Locus of control is a predictor of several other variables, such as learning achievement. The purpose of this study was to determine the relationship of locus of control with learning achievement. This research uses descriptive and correlational methods. The instrument filling is done online by using the google form application considering the increasing spread of COVID-19. Finally, as many as 36 students participated in filling this instrument. In this study, researchers used the Rotters Internal-External Locus of Control (IE Scale) inventory consisting of 29 items, of which there were 6 filler items, so that the total number of items that could be processed was 23 items, while to see learning achievement using the Grade Point Average (GPA) that researchers get from the Academic Information System (SIAKAD). Research findings show that locus of control has a strong negative relationship with student learning achievement. We advise students to have an internal locus of control while continuing to believe in God; The counselor is expected to be able to arrange an intervention program for students who have an external locus of control and have low learning achievement.